2010
DOI: 10.1007/s11033-010-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the immunoregulatory and anti-inflammatory effects of the traditional Chinese medicine “Li-Yan Zhi-Ke Granule” for relieving chronic pharyngitis in rats

Abstract: Chronic pharyngitis, a chronic inflammation of the pharyngeal mucous membrane and submucous lymphoid tissues, is often caused by unsatisfactory treatment of acute pharyngitis or repeated occurrences of upper respiratory tract infection and is related to a high-dust environment. Traditional herbal pharmacotherapy is well known for combining plant species to create complex phytochemical mixtures in the attempt to ameliorate pathophysiological processes. The aim of current study is to investigate the effect of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In a previous study, we found that 50-EFP can also be used to treat pharyngitis. Pathologies causing pharyngitis include a wide range of conditions with two primary underlying causes: inflammation and bacterial infection of pharyngeal mucosa [ 16 – 18 ]. Therefore, we investigated whether a key fraction of P. alkekengi extract known as 50-EFP has inherent antibacterial and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that 50-EFP can also be used to treat pharyngitis. Pathologies causing pharyngitis include a wide range of conditions with two primary underlying causes: inflammation and bacterial infection of pharyngeal mucosa [ 16 – 18 ]. Therefore, we investigated whether a key fraction of P. alkekengi extract known as 50-EFP has inherent antibacterial and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…The carbon particle clearance test was performed as previously described (1), but with minor modifications. Briefly, 50 mice were randomly divided into a vehicle, dexamethasone (5 mg/kg body weight per day) and three Yanshu groups (10, 20 and 40 g/kg body weight per day; n=10 per group).…”
Section: Methodsmentioning
confidence: 99%
“…The disease may also occur in response to chronic inflammation caused by alcohol abuse, overuse of the voice and cigarettes. Clinically, chronic pharyngitis manifests itself as itching, dryness, soreness of the throat, coughing and the feeling of a foreign body or obstruction in the throat (1). Chronic pharyngitis may have an infectious or non-infectious etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the discovery, development and registration of novel drugs is a costly and very lengthy process (about 10–17 years), other efforts to develop adiponectin agonists merit consideration. Furthermore, natural products have long been used to treat diseases with efficacy and drug candidates derived from natural origins may mitigate adverse biological effects [24], [25]. Therefore, we conducted a high throughput screening against a natural compounds library and identified nine lead compounds.…”
Section: Introductionmentioning
confidence: 99%